2023
DOI: 10.1088/1361-6560/acea16
|View full text |Cite
|
Sign up to set email alerts
|

Ionization detail parameters and cluster dose: a mathematical model for selection of nanodosimetric quantities for use in treatment planning in charged particle radiotherapy

Bruce Faddegon,
Eleanor A Blakely,
Lucas Burigo
et al.

Abstract: Objective: To propose a mathematical model for applying Ionization Detail (ID), the detailed spatial distribution of ionization along a particle track, to proton and ion beam radiotherapy treatment planning (RTP). Approach: Our model provides for selection of preferred ID parameters (Ip ) for RTP, that associate closest to biological effects. Cluster dose is proposed to bridge the large gap between nanoscopic Ip and macroscopic RTP. Selection of Ip is dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Therefore, finding the most accurate p and d combination requires at least a general knowledge of the size of DNA fragments important in the context of interactions with ionizing radiation and a sensible approach to assessing the resulting p value based on the chosen d. For that reason, these studies focus on R 2 for a target of 2.3 × 3.4 nm 2 . Basing on R 2 is not contrary to the approach proposing ionization details [7]. It presents the opportunity to enhance this approach using the proposed universal descriptor R 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, finding the most accurate p and d combination requires at least a general knowledge of the size of DNA fragments important in the context of interactions with ionizing radiation and a sensible approach to assessing the resulting p value based on the chosen d. For that reason, these studies focus on R 2 for a target of 2.3 × 3.4 nm 2 . Basing on R 2 is not contrary to the approach proposing ionization details [7]. It presents the opportunity to enhance this approach using the proposed universal descriptor R 2 .…”
Section: Discussionmentioning
confidence: 99%
“…We completed simulations for target sizes of (1) diameters equal to height of 0.8, 1.0, 1.3, 1.5, 1.8, 2.0, 2.3 and 2.5 nm, (2) diameters of 1.0, 2.0, and 2.3 nm, and height/diameter ratio of 1.48. The source was a pencil beam of 1 H, 4 He, 7 Li, 11 B, 12 C, 14 N, 16 O, 28 Si to provide various radiation qualities and consistency with radiobiological data. Since Geant4-DNA can only simulate ionization caused by incident ions predominant in the cosmic spectrum, direct results for 20 Ne were not available, leading to interpolation using 12 C, 14 N, 16 O, and 28 S. The interpolation method was tested for 16 O using 12 C, 14 N, and 28 S, yielding very good agreement with the result of the direct simulation for 16 O.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The I p considered in this study have been shown to closely associate with different biological endpoints independently of the particle; N 1 with cell inactivation cross-sections (Conte et al 2017), F 2 with DSB cross-sections (Nettelbeck and Rabus 2011), F 5 and F 7 with cell survival in aerobic and hypoxic conditions, respectively (Faddegon et al 2023).…”
Section: Nanodosimetrymentioning
confidence: 93%